Project management practices for collaborative university-industry R&D: a hybrid approach - Fernandes, Aldora Gabriela Gomes (2018)
This paper aims to help stakeholders involved in collaborative university-industry R&D initiatives by presenting a hybrid project management (PM) approach, with a set of key distinct PM practices for this particular context. Collaborative university-industry R&D initiatives are usually organized as programs with a set of related projects associated. Therefore, a hybrid PM approach was developed based on a case study research strategy. During the large case study analysis two research methods were applied: participant observation and document analysis. The hybrid management approach was developed based on the contingency theory, which identifies a set of 24 Must Have PM practices, and that are transversal to all projects in the program as the program governance must have to be assured. Additionally, it identifies three different sets of Nice to Have PM practices, which are optional and are dependent on the particular project context and PM approach adopted by each project team: waterfall or agile. Overall 32 Nice to Have PM practices were identified, being 15 of them agile, 3 waterfall and the 14 remaining transversal to both agile and waterfall approaches.